Initiating and Maintaining ADHD Medications in Islington CAMHS 2023 - Emmanuel Ameh (BJPsych Open)
Aims: To evaluate and improve the adherence to NICE guidelines in recording physical health parameters during the initiation and maintenance of ADHD medications.